High-Fidelity Simulation of CJ-ODW Initiation and Wave Interactions in JP-10/Air Mixtures Using a Robust Combustion Modelling Method - Wu, Yi-Jhen; Chen, Jyh-Yuan; Niu, Yang-Yao (International journal of computational fluid dynamics, 2024)
Jet Propellant 10 (JP-10), a high-energy-density fuel with a complex molecular structure, is widely utilised in advanced propulsion systems owing to its favourable volumetric energy content and thermal stability. This study employs high-fidelity numerical simulations to examine ODWs formed in JP-10/air mixtures, utilising a skeletal mechanism, a reduced mechanism, and a three-step model to analyze shock-induced ignition, heat release rates, and wave interactions. Key features, including the Chapman - Jouguet ODW (CJ-ODW), are investigated to clarify CJ-ODW initiation characteristics. Although CJ-ODWs exhibit lower strength than conventional ODWs, they still achieve the critical CJ conditions for initiation. Moreover, interactions between the first transverse wave and the second oblique shock wave distort the CJ plane, while combustion waves continue heating the reactive mixture. JP-10's endothermic behaviour during initial breakdown strongly influences this process, creating a characteristic V-shaped temperature gap and altering the reaction front structure.